Mouse Testicular Cell Type-Specific Antiviral Response against Mumps Virus Replication - Wu, Han; Zhao, Xiang; Wang, Fei; Jiang, Qian; Shi, Lili; Gong, Maolei; Liu, Weihua; Gao, Bo; Song, Chengyi; Li, Qihan; Chen, Yongmei; Han, Daishu (Frontiers in Immunology, 2017)
Mumps virus (MuV) infection has high tropism to the testis and usually leads to orchitis, an etiological factor in male infertility. However, MuV replication in testicular cells and the cellular antiviral responses against MuV are not fully understood. The present study showed that MuV infected the majority of testicular cells, including Leydig cells, testicular macrophages, Sertoli cells, and male germ cells. MuV was replicated at relatively high efficiencies in Sertoli cells compared with Leydig cells and testicular macrophages. In contrast, MuV did not replicate in male germ cells. Notably, testicular cells exhibited different innate antiviral responses against MuV replication. We showed that interferon β (IFN-β) inhibited MuV replication in Leydig cells, macrophages, and Sertoli cells, which were associated with the up-regulation of major antiviral proteins. Autophagy played a critical role in blocking MuV replication in male germ cells. Autophagy was also involved in limiting MuV replication in testicular macrophages but not in Leydig and Sertoli cells. These findings indicate the involvement of the innate defense against MuV replication in testicular cells.